Ischio-ilial Pinning for Stabilization of Coxo-femoral Luxations: An Anatomical Study - Lewis, D. D.; Beale, B. S.; Dean, P. W.; Kearney, M. T. (Veterinary and Comparative Orthopaedics and Traumatology, 1990)
Bilateral cranio-dorsal coxo-femoral luxations were created in 20 canine cadavers. After reduction, ischio-ilial pins were placed bilaterally, at one of three insertion sites ventral or ventro-lateral to the ischiatic tuberosity. Stability of the reduction was assessed before and after pin placement. All (20) pins placed in the central position prevented the femoral head from luxating to the cranio-dorsal position, while cranio-dorsal luxations occurred in two of 10 cadavers after medial pin placement and two of 10 cadavers after lateral pin placement. The pelvic region was dissected to assess the relationship of the pin to the regional anatomy. Pins placed at the central position were often in contact with the ischiatic nerve, while pins placed in the medial and lateral positions were not. Pins placed in the central position afford the greatest stability; however, they also have the greatest potential of ischiatic nerve trauma.The stability, resulting from ischio-ilial pinning, to prevent coxo-femoral luxation was studied in canine cadavers
Keywords: Coxo-femoral luxation